2015
DOI: 10.3892/mmr.2015.3689
|View full text |Cite
|
Sign up to set email alerts
|

Progress on hypoxia-inducible factor-3: Its structure, gene regulation and biological function (Review)

Abstract: Abstract. Hypoxia inducible factors (HIFs) are transcription factors, which are commonly expressed in mammals, including humans. The HIFs consist of hypoxia-regulated α and oxygen-insensitive β subunits, and are key regulators of gene expression during hypoxia in normal and solid tumor tissues. Three members of the HIF family, HIF-1α, HIF-2α, and HIF-3α, are currently known. HIF-3α differs from HIF-1α and HIF-2α in protein structure and regulation of gene expression. For a long time, HIF-3α was considered as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 69 publications
2
107
0
1
Order By: Relevance
“…HIF-1α, the most well-studied isoform, is ubiquitously expressed, while HIF-2α expression is restricted to endothelial cells, heart, lung, placenta and kidney [48]. Only recently the expression profile of the several HIF-3α spliced variants has been elucidated, with HIF-3α predominantly expressed in kidney and lung epithelial cells [49]. Interestingly, although HIF-1α and HIF-2α are structurally closely related, and despite some redundancy in their functions with the sharing of several common target genes, they also have distinct target gene cohorts [50].…”
Section: Hypoxia and Hypoxia Inducible Factor (Hif) Pathwaymentioning
confidence: 99%
“…HIF-1α, the most well-studied isoform, is ubiquitously expressed, while HIF-2α expression is restricted to endothelial cells, heart, lung, placenta and kidney [48]. Only recently the expression profile of the several HIF-3α spliced variants has been elucidated, with HIF-3α predominantly expressed in kidney and lung epithelial cells [49]. Interestingly, although HIF-1α and HIF-2α are structurally closely related, and despite some redundancy in their functions with the sharing of several common target genes, they also have distinct target gene cohorts [50].…”
Section: Hypoxia and Hypoxia Inducible Factor (Hif) Pathwaymentioning
confidence: 99%
“…1, 4 Different HIF-3 α splice variants exist, which are able to activate or repress HIF signalling depending on the cellular context. 4, 12, 13 …”
mentioning
confidence: 99%
“…Several hypoxia regulated/responsive elements located in the 5 0 and 3 0 UTR of the VEGF-A gene are involved in the fine-tuning of VEGF-A expression [26]. HIF-1a and HIF-2a are transcription factors that activate VEGF-A expression, whereas HIF-3a exerts a negative regulation of the angiogenic response by competing with HIF-1a and HIF2a binding sites [16]. In the present study, we demonstrated that let7g could bind two binding sites in the HIF-3a 3…”
Section: Discussionmentioning
confidence: 99%
“…We used the IPA software to indicate that let-7g may directly bind to HIF-3a and TP53, both of which are up-stream regulators of VEGF-A [16][17][18]. The luciferase reporter assay confirmed that HIF-3a harbours two let-7g binding sites, and let-7g could dose-dependently reduce luciferase activity ( Fig.…”
Section: Hif-3 a And Tp53 As Let-7g Target Genesmentioning
confidence: 99%